My Salinger year [videorecording (DVD)] - Falardeau, Philippe; Falardeau, Philippe; Qualley, Margaret; Weaver, Sigourney, 1949-; Booth, Douglas, 1992-; Rakoff, Joanna, 1972- (Shout! Factory, 2021)
An aspiring writer receives personal advice from reclusive author J.D. Salinger.